Methods best adapted to the teaching of domestic science in high schools - Harner, Daisy Ina (My University, 1906)
Introduction: In this thesis the pupil has first been considered, as to age, psychological conditions and previous educational advantages. There has been arranged an outline of a general course of study including twenty eight lessons, to be used as a guide in teaching Domestic Science in high schools. In presenting any subject for study or merely for an hour's entertainment the prime consideration must needs be the hearers. In teaching the pupil is essentially the teacher’s hearer, so previous to planning the work the pupils to be taught were considered. The possibilities of younger students are to a great extent controlled by the age of the individual. The average age of high school pupils is from fifteen to seventeen years. The pupil has come up through the grades where he has acquired elementary and general knowledge and is just at the stage where he is able to grasp scientific knowledge. There is a new awakening and an enlargement of capacity to receive. The mind is keen and alert. Indeed it may be characterized as the impressionable age. Successful teaching at this time presupposes a thorough grasp of method on the part of the teacher, coupled with the ability of effective presentation. Observation should be encouraged and insisted upon whenever occasion permits as a foundation and an incentive to thought and reasoning. The teacher must keep ever before her the fact that Domestic Science is truly a science, and that its genuine training value is equal in importance to its utility value. Theory, on the other hand, without practice is wholly incomprehensible to the young mind and is virtually of no value to the student, for this reason care should be taken to select experiments and practice dishes in keeping with each lesson.
Citation: Harner, Daisy Ina. Methods best adapted to the teaching of domestic science in high schools. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Domestic Science; Home Economics; Teaching; High School; Theses